(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
In this present work, we consider the algebraic operations on full fuzzy parameterized soft set and hence study some of its properties. Furthermore, we give application of this concept in solving decision making problem by developing an algorithm, which is demonstrated with a numerical example to validate the theoretical arguments.